PERBANDINGAN LAJU PERTUMBUHAN PADA PROPAGASI TANAMAN REVEGETASI TAMBANG GAMPING MENGGUNAKAN MEDIA TANAM KOMERSIAL DAN TANAH GAMPING - Giansiswi, Probowati Isworo; Titah, Harmin Sulistyaning (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2025)
Revegetation efforts on former limestone mine sites offer potential for climate change mitigation through biological CO2 absorption. However, the extreme conditions at these mining locations necessitate the validation of planting media to ensure the success of initial plant propagation. This study aimed to compare the effectiveness of commercial growth medium and limestone soil sourced from the Berkah Sari Bumi Rembang mine site as the initiation media for the early growth of revegetation plants, specifically utilizing maize (Zea mays L.) and groundnut (Arachis hypogaea L.) as test species. Generative propagation was conducted in a greenhouse for 30 days, involving physical observation and plant height measurement every 7 days. The primary parameter observed was plant height, assessed using the relative growth rate (RGR). The results showed a significant difference in growth rates between the plants grown in the two media. In the commercial growth medium, all maize and groundnut plants survived until the end of the propagation period with significant growth; the highest plant height was recorded by the BISI-2 maize variety at 51.4 cm on Day 30, with the best growth rate of 0.11 cm/week during the 14-21day period. Conversely, the limestone soil exhibited very slow growth. Most plants died before the propagation period was complete, and the only surviving plant was the BISI-2 maize variety, reaching a maximum height of only 5.5 cm on Day 14. The commercial growth medium is the recommended choice for propagation due to its sufficient nutrient content and good water retention ability, making it ideal for preparing optimal plants before they are transferred for the main study on limestone soil.